Preparation of metformin HCl microspheres and encapsulation efficiency - Ahmad, Kausar; Ruslan, Ruhaini; Mohamed, Farahidah; Elsaid Ali, Aimen Abdo (2013)

(untitled)
Due to the pharmacokinetic properties, metformin HCl needs longer period to achieve therapeutic effects with multiple daily doses which may reduce patient’s adherence towards the medication. Hence, novel drug delivery system such as microspheres may be helpful for this non-compliance of the conventional therapy. Double-emulsion solvent evaporation technique was employed in this work since Metformin HCl is a hydrophilic drug. PLGA and PVA of specific characteristics were used. A total of 30 formulations were prepared by varying the concentration of metformin and different conditions. The procedure employed resulted in spherical and free-flowing microspheres with acceptable particle size for drug delivery. Maximum encapsulation efficiency observed was 15%. The concentration of metformin used influenced the encapsulation efficiency among other factors. Higher values, which is desirable for dosage form, may be obtained by manipulating the parameters such as the molecular weight of PLGA.